2020
DOI: 10.3389/fmicb.2020.01374
|View full text |Cite
|
Sign up to set email alerts
|

CexE Is a Coat Protein and Virulence Factor of Diarrheagenic Pathogens

Abstract: CexE is a 12 kDa protein that was originally reported to be present in just three strains of enterotoxigenic Escherichia coli (ETEC); a frequent cause of diarrheal illnesses worldwide. However, an examination of sequenced genomes has revealed that CexE is actually present in a majority of ETEC strains. In addition, homologs of CexE are present in enteroaggregative E. coli (EAEC), Yersinia enterocolitica, Providencia alcalifaciens, and Citrobacter rodentium. Although it has been hypothesized that CexE and its h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…The λ Red recombinase system 47 was used to generate a rns knockout in ETEC 1392/75-2a similarly to the cfaD::kan H10407 strain previously described 48 . Primers 1242/1150 were used to amplify a tetracycline resistance cassette targeting rns from pAH162.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The λ Red recombinase system 47 was used to generate a rns knockout in ETEC 1392/75-2a similarly to the cfaD::kan H10407 strain previously described 48 . Primers 1242/1150 were used to amplify a tetracycline resistance cassette targeting rns from pAH162.…”
Section: Methodsmentioning
confidence: 99%
“…PVDF membranes were blocked in TBS-Blotto (25 mM TrisCl pH 7.6, 150 mM NaCl, 5% wt/vol powdered nonfat milk). Antibodies against CexE homologs CexEα (H10407) and CexEε (1392/75-2a) were produced by immunization of rabbits (Proteintech Group, Inc.) with purified antigens and used at a dilution of 1:5000 in TBS-Blotto with 0.05% vol/vol Tween20 45 , 48 . The primary antibody against DnaK (AbCam ab69617) was used at a 1:10,000 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…The conservation of this system within pathogenic bacterial strains represents a possible new drug target. Previous studies have shown that deletion of aatD, aatC, or aap/cexE reduces bacterial colonisation and disease (11,12). Thus, chemicals targeting the Aat system have the potential to prevent or perhaps reduce the severity of bacterial disease.…”
Section: Discussionmentioning
confidence: 99%
“…The full Aat system and an Aap or CexE homolog was identified in 826 separate nucleotide accessions (Supplementary Table S1). This revealed that the Aat system is distributed more widely than initially anticipated and is encoded in pathogens with diverse mechanisms of virulence such as ETEC, EAEC, enteropathogenic E. coli, Shiga-toxin producing E. coli, Shigella sp., Salmonella enterica, Citrobacter rodentium, Providencia alcalifaciens and Yersinia entercolitica (10,11,16).…”
Section: Distribution Of the Aat Systemmentioning
confidence: 99%
See 1 more Smart Citation